One method of approximate fractional differentiation for traffic analysis - Денисюк, В. П.; Рибачук, Л. В. (Problems of Informatization and Control, 2009)
Several problems of approximate calculation of fractional derivatives in the Riemann- Liouville sense are considered. The method of analytical change is used in which a function is approximated by algebraic polynomials. The formulae and errors estimations of fractional differentiation in the C-metric are presented